New ant species related to Cerapachys sexspinus and discussion of the status of Yunodorylus (Hymenoptera: Formicidae) - Borowiec, Marek L. (Zootaxa, 2009)
Three species related to the Chinese ant Cerapachys sexspinus (Xu, 2000) are described as new: Cerapachys doryloides n. sp. from Borneo, C. eguchii n. sp. from Vietnam, and C. paradoxus n. sp. from Borneo. Additionally, Cerapachys sexspinus is redescribed. A species-group diagnosis and a discussion of the group’s affinities are provided, together with a key to species based on workers. All species are illustrated with photographs and a distribution map. It is recommended that the name Yunodorylus remain a synonym of Cerapachys until the taxonomy and phylogeny of the Cerapachyinae is better understood.